Minimal invasive methods of diagnostic and treatment of facet-syndrome pain (literature review) - Perfiliev, Olexandr; Radchenko, Volodymyr; Kutsenko, Volodymyr; Popov, Andrey; Skidanov, Artem; Piontkovsky, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Purpose: on the basis of the analysis of the scientific literature, to study the most significant problems of interventional methods of diagnosis and treatment of painful facet syndrome in lumbar spondylarthrosis, and to determine the ways of their solution. Methods: publications for the last 20 years from electronic databases PubMed, MEDLINE, articles, monographs, authors abstracts, dissertations and other sources of scientific and medical information have been studied. 178 publications on the lumbar pain facet syndrome, 199 — lumbar medial branches of the posterior branches of the spinal cord nerves, 1 062 — blockade and denervation of the lumbar arched joints, 7 — their endoscopic denervation. 74 publications with II and III levels of evidence were selected. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> an increase in the prevalence of the use of minimally invasive diagnostic blockades and denervation of the facets in the lumbar spine resulted in an increase in the number of not only positive, but also unsatisfactory results. It has been established that the innervation of facets has individual anatomical and topographical features of the location of the nerves, which can influence the results of minimally invasive methods of treatment of the facet syndrome. Selective blockages of the medial branches of the posterior branches of the spinal nerves and intra-articular blockade of the facets, with observance of qualitative control, are effective for short-term treatment of the chronic painful facet syndrome, and denervation of the facets in the form of a neurotomy of the said branches under endoscopic control is the most successful method for achieving long-term The main ways of improving minimally invasive methods for diagnosis and treatment of painful facet syndrome of lumbar spondylarthrosis have been found.